2005
DOI: 10.1007/s00380-004-0800-x
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive protein elevation predicts the occurrence of atrial structural remodeling in patients with paroxysmal atrial fibrillation

Abstract: It has been poorly understood whether inflammation may contribute to atrial structural remodeling and increase the propensity for atrial fibrillation (AF) to persist. We investigated the relationship between C-reactive protein (CRP) elevation and the development of atrial remodeling in AF. The study population comprised 50 consecutive paroxysmal AF (PAF) patients and 50 control patients without AF. All patients underwent echocardiography, and high-sensitivity CRP was routinely measured. C-Reactive protein was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
2
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 17 publications
1
72
2
6
Order By: Relevance
“…[34][35][36] It has been recently shown that atrial structural remodelling, assessed by left atrial diameter, correlated positively with hsCRP levels in patients with PAF. 23,37,38 Such a relation, however, was not supported by our results. A possible explanation could be the difference in the way we assessed left atrial size, by measuring left atrial volume instead of atrial diameter.…”
Section: Discussioncontrasting
confidence: 99%
“…[34][35][36] It has been recently shown that atrial structural remodelling, assessed by left atrial diameter, correlated positively with hsCRP levels in patients with PAF. 23,37,38 Such a relation, however, was not supported by our results. A possible explanation could be the difference in the way we assessed left atrial size, by measuring left atrial volume instead of atrial diameter.…”
Section: Discussioncontrasting
confidence: 99%
“…267,[483][484][485] Recently, giant-cell myocarditis involving only the atria has been shown to result in atrial fibrillation with enlarged atria. 149 Patients with apparently lone atrial fibrillation frequently demonstrate histological findings consistent with an atrial myocarditis; 486 and those with past myocarditis may have atrial electrical scar, conduction abnormalities, or atrial standstill.…”
Section: Role Of Myocarditismentioning
confidence: 99%
“…In a multivariate analysis of The Cardiovascular Health Study that included 5806 individuals, CRP levels predicted both the presence of AF at baseline and the development of AF during followup, even after adjustment for potential confounding factors [7] . Moreover, longer duration of AF has been found to be associated with higher hs-CRP levels compared with shorter duration of AF, which indicates that there is a link between AF burden and systemic inflammation [8,15] . Similarly, hs-CRP has been found to be a significant predictor of early AF recurrence after cardioversion [11,[16][17][18][19][20] .…”
Section: Pathophysiologymentioning
confidence: 99%